2013
DOI: 10.1007/s12275-013-3279-2
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus paracasei subsp. paracasei LC01 positively modulates intestinal microflora in healthy young adults

Abstract: Lactobacillus paracasei subsp. paracasei LC01 (LC01) can tolerate intestinal stresses and has antioxidant activity. To evaluate the effect of the bacterium on human intestinal microflora, a randomized, double-blind, placebo-controlled human trial was carried out. Fifty-two healthy adult volunteers were randomized equally to two groups. One group consumed 12% (wt/vol) skimmed milk supplemented with 10(10) CFU of LC01 each day for the 4-week treatment period, and then consumed placebo in the next treatment perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…Ameliorating the intestinal dysbiosis with prebiotics and probiotics have gained considerable attention in recent years for the management of MetS [45]. However, the studies have yielded inconsistent results regarding the influence of probiotics on fecal microbial diversity and composition [46,47,48,49,50,51,52]. Furthermore, the effects of kefir as a probiotic on gut microbiota have been examined very limited and mainly with animal studies.…”
Section: Discussionmentioning
confidence: 99%
“…Ameliorating the intestinal dysbiosis with prebiotics and probiotics have gained considerable attention in recent years for the management of MetS [45]. However, the studies have yielded inconsistent results regarding the influence of probiotics on fecal microbial diversity and composition [46,47,48,49,50,51,52]. Furthermore, the effects of kefir as a probiotic on gut microbiota have been examined very limited and mainly with animal studies.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding changes in the levels of bacteria taxonomically related to the ingested probiotic strains, the most common finding in the reviewed studies is the increase in the fecal Lactobacillus [ 39 , 45 , 47 , 48 , 49 , 50 , 54 ] or Bifidobacterium levels [ 41 , 49 , 50 ], particularly after the intake of Lactobacillus strains, suggesting the existence of bacterial cross-feeding mechanisms in the intestinal niche. In this respect, there is evidence that some Lactobacillus strains can either degrade dietary carbohydrates or host mucin polysaccharides.…”
Section: Dietmentioning
confidence: 99%
“…Probiotics, such as Lactobacillus spp. and Bifidobacterium spp., are reported multiple potential health benefits including blocking gastroenteric pathogens, enhancing immune responses, and neutralizing viruses (Rolfe, 2000;Minocha, 2009;Zhang et al, 2013). Preidis et al (2011) and Sur et al (2011) reported that probiotics such as Lactobacillus rhamnosus, L. casei, Bifidobacterium bifidum, and Streptococcus thermophilus promote the innate immune response and stimulate cellular multiplication of epithelial cells.…”
Section: Introductionmentioning
confidence: 99%